1997
DOI: 10.1007/s11606-006-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Clostridium difficile Stool Cytotoxin Results in Hospitalized Patients with Diarrhea

Abstract: OBJECTIVE: To validate a model for the prediction of Clostridium difficile cytotoxin assay results, and to identify a subgroup of patients with a very low likelihood of C. difficile -associated disease in whom the yield of routine cytotoxin testing is low. DESIGN:Prospective cohort study. Relevant clinical symptoms, signs, and antibiotic exposure were recorded before reporting of assay results. Each predictor was assigned a score based on regression coefficients, and patients were stratified according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Numerous studies identifying risk factors for C. difficile diarrhea have been published and clinical prediction rules to optimize cytotoxin testing for C. difficile in hospitalized patients with diarrhea have previously been developed and validated. 1023 ' 24 We are unaware of any previous study designed to allow stratification of antibiotic recipients at the time of hospital admission according to their risk for C. difficile diarrhea. Because of the prospective design of this study, all cases of C. difficile diarrhea in the study population were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies identifying risk factors for C. difficile diarrhea have been published and clinical prediction rules to optimize cytotoxin testing for C. difficile in hospitalized patients with diarrhea have previously been developed and validated. 1023 ' 24 We are unaware of any previous study designed to allow stratification of antibiotic recipients at the time of hospital admission according to their risk for C. difficile diarrhea. Because of the prospective design of this study, all cases of C. difficile diarrhea in the study population were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the derivation set, 5 both maximum temperature (on the index date) and comorbidity score were nearly equivalent for testpositive and test-negative subjects, and thus were not assessed in the current study. Although some hospital units had episodic clusters of cytotoxin-positive cases, utilization of the cytotoxin assay remained relatively constant throughout medical and surgical units of both hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…3 The most widely used method for diagnosis of C. difficile -associated disease is based on detecting a cytotoxin produced by C. difficile by means of a tissue culture assay. 4,5 The yield of C. difficile toxin testing in hospitalized patients with diarrhea has been reported to be approximately 20% in patients hospitalized longer than 3 days. [6][7][8][9] Other investigators, however, have suggested that approximately 40% of testing for C. difficile could be eliminated by using selective criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent pro-spective analysis of factors predicting a positive C difficile toxin in the stool indicated usefulness of the following predictive parameters: cephalosporin use, prolonged hospital stay, onset of diarrhea six or more days after receiving antibiotics, fecal leucocytes in the stool and presence of semiformed stool (6). A study to identify patients with a very low likelihood of C difficile-associated diarrhea found that patients without a history of antibiotic use or significant diarrhea or abdominal pain were unlikely to have a positive C difficile toxin assay (9). Stool tests: A good review of diagnostic tests has been published recently by Brazier (10).…”
Section: Diagnosismentioning
confidence: 99%